Home Follow-ups:Support to Classroom-Based Remediation in Enhancing Reading Comprehension - Lopez, Trisha Aira Navarro; Garcia, Mylene Cruz (English Education Department at FKIP Nommensen University, 2024)
Abstract In the educational realm, all stakeholders must take part in the overall well-being of students, regardless of their age, economic status, abilities, and individual uniqueness. Teachers are at the forefront of keeping the process going; parents are on the side, especially when supplemental assistance must be provided to the learners. This study aimed to understand home follow-ups in support of classroom-based remediation in enhancing reading comprehension skills through the lived experiences of five parents involved in their child’s learning. The study was anchored on the data gathered through a semi-structured interview to deeply understand the parents’ side on this topic. Through an Interpretative Phenomenological Analysis qualitative approach, the researchers divulged how parents’ involvement takes hold of their child’s performance in school. In this paper, five superordinate themes with corresponding sub-ordinate themes were determined: the spectrum of parents’ impressions on the idea of classroom-based remedial sessions; help given at home through follow-up sessions; reasons of parents for stepping up and taking extra actions; the difficulties and challenges encountered; and the essence of home follow-ups to the students’ holistic being. The experiences of parents revealed that home follow-ups positively impact the child, and this is a practice every parent must endeavor.